Multisystem inflammatory disorder in children and kawasaki disease in the course of the SARS-COV-2 pandemic - Lopes Machado, Gabriela Stefany; Carvalho Lima, Vitor; Ribeiro Bicudo, Lucilene Arilho (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
After the onset of the new SARS-CoV-2 coronavirus pandemic, several countries reported an increase in cases of Kawasaki Disease (KD) in the pediatric centers. KD, also called mucocutaneous lymph node syndrome, presents as an acute, multisystem pediatric vasculitis of unknown etiology. In this present study, we research to determine the influence of SARS-CoV-2 on the manifestation of KD, the overlap with the so-called Multisystem Inflammatory Syndrome in children (MIS-C) and to compare the main characteristics of these pathologies, since this relationship was evidenced throughout the year of 2020 with pediatric patients infected with coronavirus. To carry out the work, it was performed a systematic review in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses - PRISMA. Articles published or pre-published in the PubMed and Scielo databases in 2020 were considered. A total of 924 scientific articles were identified, and after excluding duplicates from the selection and data extraction, 52 remained for data comparison. None of the analyzed parameters, such as clinical manifestation, age of affected patients, laboratory variants showed a significant difference between the two groups, associated with the fact that there was no increase in the number of KD cases in the absence of concomitant SARS-CoV-2 infection, compared to pre-pandemic period. Thus, we conclude that MIS-C and KD concomitant with Coronavirus Disease 2019 (COVID-19) were named without technical criteria given the urgency in publishing information during the period of severity of the COVID-19 pandemic. KEY WORDS: COVID-19; SARS-CoV-2; Kawasaki Disease; Multisystem Inflammatory; Syndrome in children.